Enhanced photocurrent performance of partially decorated Au nanoparticles on ZnO nanorods based UV photodetector. (July 2019) - Khan, Rizwan; Uthirakumar, Periyayya; Kim, Tae Hwan; Lee, In-Hwan
Graphical abstract: A facile solution route is proposed to prepare relatively low aspect ratio ZnO nanorods (NRs) and subsequently gold nanoparticles (Au NPs) were partially decorated on the surface of ZnO NRs (Au-ZnO NRs). The partially decorated Au NPs on the surface of the relatively low aspect ratio ZnO NRs shows an enhanced band-edge emission due to the surface plasmon resonance quenching of deep level defect emission, as compared to bare ZnO NRs. The UV photodetector fabricated with Au-ZnO NRs showed a remarkable enhancement in photocurrent owing to the Au modification that leads to have a strong absorption with an improved interfacial charge separation processes. Highlights: A simple solution method for growing the relatively low aspect ratio ZnO NRs and Au-ZnO NRs. Compared to ZnO NRs, the Au-ZnO NRs demonstrated an enhanced intrinsic emission by suppressing the deep-level emission. A significant enhancement in photocurrent was observed due to the strong absorption and improved charge separation process. The low aspect ratio Au-ZnO NRs could be a potential candidate for fabricating optoelectronic devices.and improved charge separation process. Abstract: The surface modification is essentially required to develop a variety of hybrid zinc oxide (ZnO) nanostructures for fabricating optoelectronic devices. A facile solution method was proposed to prepare the relatively low and high aspect ratio ZnO nanorods (NRs) and subsequently decorated with gold nanoparticles (Au NPs) partially on the surface of ZnO NRs. The Au-ZnO NRs exhibited an enhanced band-edge emission due to the surface plasmon resonance quenching of deep level defect emission, as compared to bare ZnO NRs. The UV photodetector with the relatively low aspect ratio Au-ZnO NRs showed a lower photocurrent in dark. However, after UV light illumination, a remarkable enhancement in photocurrent owing to the Au modification was observed, which leads a strong absorption and an improved interfacial charge separation process. Hence, the relatively low aspect ratio Au-ZnO NRs provides a channel for fabricating a high performance UV photodetector, in the near future.